Entomological study in an anthroponotic cutaneous leishmaniasis focus in Morocco: Fauna survey, Leishmania infection screening, molecular characterization and MALDI-TOF MS protein profiling of relevant Phlebotomus species - Mhaidi, Idris; Ait Kbaich, Mouad; El Kacem, Sofia; Daoui, Othmane; Akarid, Khadija; Spitzova, Tatiana; Halada, Petr; Dvorak, Vit; Lemrani, Meryem (Transboundary and emerging diseases, 2022)
In Morocco, leishmaniases are a major public health problem due to their genetic diversity and geographical distribution. Cutaneous leishmaniasis (CL) is an infectious disease caused by various species of Leishmania and transmitted typically by bite of phlebotomine sand flies. This study identifies sand fly fauna in Ibaraghen village, province of Azilal, which is a focus of CL, by combination of morphological and molecular methods (sequencing of COI gene, MALDI-TOF MS protein profiling). Nested-kDNA PCR was used to detect and identify Leishmania species within potential vector species. 432 CDC light traps were placed at different heights above ground level at four capture sites during a whole year. Traps at 1.5 m above the ground yielded capture of sand flies almost double compared to above ground level (29.33%), while the collection reached 55.09% when the traps were placed 2.5 m above ground. A total of 2,830 sand flies were collected, 2,213 unfed specimens were morphologically identified, 990 males (44.73%) and 1,223 females (55.26%) of 13 species; ten Phlebotomus species and three Sergentomyia species. Six species were analysed by MALDI-TOF MS protein profiling (4 Phlebotomus and 2 Sergentomiya species), and their identification was confirmed by COI sequencing. 1,375 unfed females were screened for the presence of Leishmania by nested-kDNA PCR in pools, 11/30 pools of P. sergenti showing a single band of 750 bp corresponding to L. tropica. Our results confirm the role of P. sergenti as a proven vector in Azilal focus of cutaneous leishmaniasis; however, the relative abundance of other species known as vectors of Leishmania species emphasizes the risk of introduction of L. infantum and L. major in this province. For the first time in Morocco, a combined approach to identify sand flies by both morphology and molecular methods based on DNA barcoding and MALDI-TOF MS protein profiling was applied.
Keywords: Maroko; sand fly; Insect Vectors; Phlebotomus; kinetoplastová DNA; Female; Morocco; leishmanióza kožní; zvířata; molecular screening; cutaneous leishmaniasis; Leishmaniasis, Cutaneous; ženské pohlaví; hmyz - vektory; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Male; proteomic identification; Leishmania; Animals; mužské pohlaví; Psychodidae; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; leishmania tropica; DNA, Kinetoplast